Mental Model of Prospective Teachers on Structure and Properties Correlation of Organic Compounds - Suja, I W; Redhana, I W; Sudria, I B N (Journal of physics. Conference series, 2020)
This study aims to determine the profile of prospective teachers' mental models on the correlation of structure and properties of organic compounds before and after learning by implementing the TripleChem learning model. Subjects were students of the Chemistry Education Department of Ganesha University of Education, who are taking courses in Organic Chemistry I in 2018/2019. The subjects of the study were 22 people. Data were collected through two tier achievement test, consists content part (multiple choice) and reason (description). The data were analyzed descriptively. The results showed the mental models of prospective teachers before learning only 1.36% classified as a conceptual model. After learning by implementing TripleChem learning models, conceptual models increased to reach 62.73%. The students' alternative mental models before and after the study, including specific misconceptions (21.82% and 8.64%), and partially correct (31.36% and 28.64%). The data show that the TripleChem learning model can construct chemistry mental model of prospective teachers on the correlation of structure and properties of organic compounds.